Relationship Between Iron Deficiency Anaemia With Cognitive Function And Academic Performance Of The Primary School Children In Bachok, Kelantan - PPSK, Pusat Pengajian Sains Kesihatan (2012)
Iron deficiency anaemia (IDA) is the most common micronutrient deficiency in the world and it affects millions of children worldwide. IDA may leads to serious health problems such as poor cognitive and motor development As well as poor behavior in children. The main objective of the study was to investigate the relationship between IDA with cognitive function of the school children.